2000
DOI: 10.1097/00000658-200010000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Gut-Derived Sepsis Occurs When the Right Pathogen With the Right Virulence Genes Meets the Right Host

Abstract: Lethal gut-derived sepsis may occur when intestinal pathogens express virulence determinants in response to environmental signals indicating host stress. In this regard, the PA-I lectin/adhesin of P. aeruginosa appears to be a specific example of in vivo virulence expression in colonizing pathogens in the intestinal tract in response to surgical stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
150
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 30 publications
3
150
0
1
Order By: Relevance
“…Increased direct release of catecholamines by the enteric nervous system (ENS) under stress has also been demonstrated experimentally by Zhou et al who showed that in the GI tract of rats expression of tyrosine hydroxylase (the rate limiting enzyme of catecholamine biosynthesis; see Figure 1) became up-regulated in response to physical stress such as surgical perforation of the bowel (Zhou et al, 2004). A related study by Alverdy et al employed a mouse model of surgical stress (a partial hepatectomy v. a sham laparotomy) to show that surgery can cause direct increases in the levels of NA released into the GI tract (Alverdy et al, 2000). Alverdy and colleagues also reported that mice subjected to the partial hepatectomy became significantly more susceptible to gut-derived sepsis by the opportunistic pathogen Pseudomonas aeruginosa, possibly because of NA-induced increases in the expression of the PA-I lectin, an essential P. aeruginosa host attachment factor (Alverdy et al, 2000).…”
Section: Microbial Endocrinologymentioning
confidence: 99%
See 1 more Smart Citation
“…Increased direct release of catecholamines by the enteric nervous system (ENS) under stress has also been demonstrated experimentally by Zhou et al who showed that in the GI tract of rats expression of tyrosine hydroxylase (the rate limiting enzyme of catecholamine biosynthesis; see Figure 1) became up-regulated in response to physical stress such as surgical perforation of the bowel (Zhou et al, 2004). A related study by Alverdy et al employed a mouse model of surgical stress (a partial hepatectomy v. a sham laparotomy) to show that surgery can cause direct increases in the levels of NA released into the GI tract (Alverdy et al, 2000). Alverdy and colleagues also reported that mice subjected to the partial hepatectomy became significantly more susceptible to gut-derived sepsis by the opportunistic pathogen Pseudomonas aeruginosa, possibly because of NA-induced increases in the expression of the PA-I lectin, an essential P. aeruginosa host attachment factor (Alverdy et al, 2000).…”
Section: Microbial Endocrinologymentioning
confidence: 99%
“…A related study by Alverdy et al employed a mouse model of surgical stress (a partial hepatectomy v. a sham laparotomy) to show that surgery can cause direct increases in the levels of NA released into the GI tract (Alverdy et al, 2000). Alverdy and colleagues also reported that mice subjected to the partial hepatectomy became significantly more susceptible to gut-derived sepsis by the opportunistic pathogen Pseudomonas aeruginosa, possibly because of NA-induced increases in the expression of the PA-I lectin, an essential P. aeruginosa host attachment factor (Alverdy et al, 2000).…”
Section: Microbial Endocrinologymentioning
confidence: 99%
“…Furthermore, although P. aeruginosa is better known as a respiratory pathogen rather than an intestinal pathogen, this strain is one of the most common opportunistic pathogens in the normal gastrointestinal tract (Alverdy et al, 2000), and in critically-ill and immunocompromised Resistance to antivirulence compounds T Maeda et al patients where stress levels are high, Pseudomonas sp. counts have been shown to increase by as much as 100-fold (Shimizu et al, 2006) leading to the expression of virulence determinants (Alverdy et al, 2000) that are controlled by QS (Hegde et al, 2009) (just the presence of P. aeruginosa in the gastrointestinal tract of critically-ill surgical patients has been associated with nearly 70% mortality (Alverdy et al, 2000)). Hence, growth on this carbon source is physiologically relevant and P. aeruginosa infections in the gastrointestinal tract are pertinent.…”
Section: Introductionmentioning
confidence: 99%
“…The opportunistic pathogen Pseudomonas aeruginosa synthesizes two lectins, LecA and LecB (also known as PA-IL and PA-IIL), with specificity for galactose and fucose, respectively. Many roles have been suggested for these lectins, including adhesion of the bacterium to airway epithelial cells and injury to cells (1,15). Furthermore, LecB was recently reported to be involved in biofilm formation (27).…”
mentioning
confidence: 99%